Cognitive processes and information technology in sports: current trends and future directions - Muhammad Omer Zia; Darchia Maia, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The primary goal of this research project is to identify the cognitive processes and information technologies associated with sports. This research study defined present trends and their future directions. For this purpose, research based on secondary data analysis was conducted, and many websites relevant to cognitive processes and information technology were utilized. E-views software was utilized to measure the research study and produce useful data related to the variables. The key independent variable is cognitive processes, while the dependent variable is information technology. The research study includes descriptive statistic analysis, unit root test analysis, and an explanation of the histogram and state analysis. The study found a strong and positive connection between cognitive processes and information technology in sports.